Enhancing Arabic speaking skills among Malay students through group work activities - Noor Anida, Awang; Misrah Hamisah, Mohamed; Ruhaizan, Sulaiman@Abd. Rahim (2013)
This study aims to investigate strategies for Arabic speaking skills enhancement through group work activities. It highlights the effectiveness of group work activities in teaching Arabic speaking skills among first year Malay undergraduate university students studying Arabic language. Data were collected through semi-structured interviews with five students, group discussions and direct observations on twenty students. The findings of the study indicated that group work activities have a crucial impact on speaking foreign language skills. They help to increase the level of confidence among students who are shy, easily get panic and fear of speaking Arabic language in front of peers. Group work activities are effective to develop speaking skills among students but it is depending on how the lecturer implements group work activities in teaching and learning Arabic as a foreign languag